PENGAWASAN DINAS LINGKUNGAN HIDUP DAN KEBERSIHAN KOTA PEKANBARU DALAM PENGENDALIAN PENCEMARAN DAERAH ALIRAN SUNGAI (DAS) SIAK KOTA PEKANBARU TAHUN 2017 - Habibullah Masri; Baskoro Wicaksono (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The Siak River is one of the major rivers that has received national attention and is also included in the national strategic river category (Kepres No. 12 tahun 2012).The number of activities in the Siak watershed, including as a means of transportation, agricultural water sources, clean water sources, and business activity centers, and so on causing the water quality standard in the Siak watershed to decline. This research is motivated by how the supervision carried out by the Department of Environment and Sanitation of Pekanbaru City but under their supervision they encountered various problems. The purpose of this study is to analyze the problems that occur in the implementation of supervision which causes a decrease in the quality of water quality standards in the Siak Watershed in Pekanbaru City. The method used in this research is descriptive method with qualitative research type. The types of research data are primary data and secondary data. The data collection technique in this research is documentation and interviews. The data analysis technique used is descriptive qualitative data analysis.The results showed that the monitoring of DLHK in controlling the pollution of the Siak Watershed in Pekanbaru City has not been optimal. This can be seen from the decline in the quality of water quality standards in the Siak Watershed in Pekanbaru City. There are inhibiting factors both internally and externally; provision of inefficient facilities and infrastructure and no coordination between institutions on a par. The right solution to overcome the problems in controlling pollution in the Siak Watershed in Pekanbaru City is to create a neater and more effective program planning, and creating policies that can improve coordination between each agency concerned and the community, increase the budget, and increase the time for more intensive and routine monitoring.  Keywords : monitoring, regulatory compliance inspection, inter-agency coordination